Designing Indonesian Maternal and Child Health Mobile Applications using User-Centered Design - Achmad Fikri Adidharma; Nadya Shelim; Shanika Tysha Anqita; Putu Wuri Handayani (Faculty of Computer Science Universitas Indonesia, 2024)
The high maternal mortality rate in Indonesia has led the Indonesian government to develop a mobile application for maternal and child health (MCH). However, this application received a bad rating on the applications distribution platform, and even some of its features could not function properly. Therefore, this study aims to design the MCH application. This study used the user-centered design (UCD) methodology with three iterations and applied Shneiderman's eight golden rules. Participants involved in the data collection and evaluation process were health workers, health experts, and pregnant women. The first iteration's evaluation will produce a low-fidelity prototype (wireframe), whereas the second and third iteration's evaluations will produce a refined high-fidelity clickable prototype. The resulting prototype has several major features, including notes entry, information and education, reminders, a blood supplement tablet tracker, and monitoring of fetal development. Evaluation in the first iteration utilized interviews to validate the wireframe, whereas the second and third iterations utilized usability testing and system usability scale (SUS). In the second iteration, the final SUS score was 71.2, or